PENGARUH REPUTASI, LOKASI, DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI CAFE RUMAH SAKIT WIYUNG SEJAHTERA SURABAYA - Rohulloh Yusuf Arqom (KELOMPOK KOMUNITAS LABORATORIUM PENELITIAN, 2022)
Currently the development of the Cafe business has penetrated in various areas, one of which is in the city of Surabaya. This is evidenced by the increasing number of business people who start or develop their cafe business. In maintaining their existence in the business world, business people must always be responsive and adapt in the face of competition, including influencing consumer purchasing decisions on various alternatives offered in the market. The purchase decision can be influenced by several factors, such as reputation, location, and service quality. Therefore, this study aims to determine and analyze the influence of reputation, location, and service quality on consumer purchasing decisions. This research is a type of quantitative research. The object of this research is the consumers of Cafe RS. Wiyung Sejahtera with a sample of 100 respondents selected using a non-probability sampling technique with purposive sampling. Data collection techniques in this study using a questionnaire and will then be analyzed. The data analysis technique used in this research is multiple linear regression, correlation test, determination test, F test, and t test with the help of SPSS application. The results obtained in this study include: 1) reputation, location, and service quality influence simultaneously or jointly on consumer purchasing decisions at Cafe RS. Wiyung Sejahtera by obtaining a result of 0.000 <0.05 on the F test (simultaneously); 2) reputation and service quality variables have a positive and significant influence on purchasing decisions; 3) the location variable does not have a positive and significant effect on purchasing decisions.